Subjective experiences of transient ischaemic attack: a repertory grid approach. (December 2013) - Spurgeon, Laura; James, Gill; Sackley, Cath
Abstract Purpose: Research on the psychosocial reactions to stroke has been used to inform rehabilitation programmes. Yet much less research has been conducted into experiences of, and reactions to, transient ischaemic attack (TIA), despite its link with secondary stroke. This study aimed to investigate the subjective psychological experiences of TIA. Method: Repertory grid technique was used because of its capacity to make individual implicit experiences explicit. Using the standard repertory grid protocol, 12 post-TIA patients were asked to consider how five everyday activities had been affected by TIA. Each participant generated six constructs or personal perspectives, which were analysed using proprietary (RepGrid IV) software. Results: Despite the individualised nature of the responses, six themes emerged from the constructs. These included deep-seated anxiety about future uncertainties/disruption to normality, loss of confidence, frustration, TIA as a wake-up call, a sense of loss and sadness, and embarrassment. Implications for Rehabilitation Research has shown that the patient's subjective experience and perspective are important to the rehabilitation process post-stroke. Relatively little research has been conducted into the subjective experiences of TIA patients. This study has revealed a range of subjective reactions to TIA, which could be used to inform individualised post-TIA management, adaptation and rehabilitation.